Cigarette Smoking in Indonesia: Examination of a Myopic Model of Addictive Behaviour - Hidayat, B. (2012)
Using aggregated panel data taken from three waves of the Indonesian Family Life Survey (1993-2000), this article tests the myopic addiction behaviour of cigarette demand. Sensitivity analysis is done by examining a rational addiction behavior of cigarette demand. The results provide support for myopic addiction. The short- and long-run price elasticities of cigarette demand are estimated at -0.28 and -0.73 respectively. Excise taxes are more likely to act as an effective tobacco control in the long-run rather than a major source of government revenue.